EMPOWERMENT OF MIDWIVES AS DIGITAL HEALTH INFORMATION AGENTS AS AN EFFORT TO SAVE MOTHERS AND NEWBORN BABIES - Nursanti, Siti; Tayo, Yanti; Setyastuti, Yuanita; Yunidharta, Firdaus; Sulistiyowati, Nina (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The advancement of communication and information technology in Indonesia has become one of its strengths for handling maternal and infant mortality in Indonesia; with good skills in managing information using advanced technology and information sources from a midwife, the public will more easily recognize the signs of an emergency felt by pregnant women. and will give birth. This community service activity is carried out to increase the knowledge and ability of midwives to manage sources of maternal and newborn health information. The activity was carried out in Waluya District, Karawang Regency, and was attended by 20 midwives in the area. The activity found an increase in the knowledge and ability of midwives to manage digital information by 40%.